Anti-Müllerian Hormone: A Molecular Key to Unlocking Polycystic Ovary Syndrome? - Abbott, David H.; Hutcherson, Beverly A.; Dumesic, Daniel A. (Seminars in Reproductive Medicine, 2024)
Anti-Müllerian hormone (AMH) is an important component within androgen receptor (AR)-regulated pathways governing the hyperandrogenic origin of polycystic ovary syndrome (PCOS). In women with PCOS, granulosa cell AMH overexpression in developing ovarian follicles contributes to elevated circulating AMH levels beginning at birth and continuing in adolescent daughters of PCOS women. A 6 to 7% incidence among PCOS women of gene variants coding for AMH or its receptor, AMHR2, suggests genetic contributions to AMH-related pathogenesis. Discrete gestational AMH administration to pregnant mice induces hypergonadotropic hyperandrogenic, PCOS-like female offspring with high circulating AMH levels that persist over three generations, suggesting epigenetic contributions to PCOS through developmental programming. Moreover, adult-onset, selective hyperactivation of hypothalamic neurons expressing gonadotropin-releasing hormone (GnRH) induces hypergonadotropic hyperandrogenism and PCOS-like traits in female mice. Both gestational and adult AMH inductions of PCOS-like traits are prevented by GnRH antagonist coadministration, implicating luteinizing hormone–dependent ovarian theca cell testosterone (T) action, mediated through the AR in AMH-induced pathogenesis. Interestingly, gestational or peripubertal exogenous T or dihydrotestosterone induction of PCOS-like traits in female mice, rats, sheep, and monkeys fails to elicit ovarian AMH hypersecretion; thus, AMH excess per se may lead to a distinct pathogenic contribution to hyperandrogenic PCOS origins.
Keywords: neuronal AMH; overexpression of AMH; developmental programming; PCOS etiology; animal models